2018
DOI: 10.3390/fib6010012
|View full text |Cite
|
Sign up to set email alerts
|

Restrained Shrinkage Cracking of Fiber-Reinforced High-Strength Concrete

Abstract: Concrete shrinkage and volume reduction happens due to the loss of moisture, which eventually results in cracks and more concrete deformation. In this study, the effect of polypropylene (PP), steel, glass, basalt, and polyolefin fibers on compressive and flexural strength, drying shrinkage, and cracking potential, using the ring test at early ages of high-strength concrete mixtures, was investigated. The restrained shrinkage test was performed on concrete ring specimens according to the ASTM C1581 standard. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…So, when tensile cracking dominates concrete behaviour, it is required to use appropriate additions with a strain-hardening response under tensile loading [31,32]. Fibres are known for their tensile strength capacity and they have been widely used to improve the resistance to tensile stress and concrete spalling [33][34][35][36]. So, the tensile and flexural strength of concrete materials can be remarkably improved by adding a low volume of fibres, while a moderate increase can occur in the compressive strength of fibre reinforced concrete due to a high strain-hardening response of fibres under tensile loading.…”
Section: Concrete Is One Of Most Popular Construction Materials and Imentioning
confidence: 99%
“…So, when tensile cracking dominates concrete behaviour, it is required to use appropriate additions with a strain-hardening response under tensile loading [31,32]. Fibres are known for their tensile strength capacity and they have been widely used to improve the resistance to tensile stress and concrete spalling [33][34][35][36]. So, the tensile and flexural strength of concrete materials can be remarkably improved by adding a low volume of fibres, while a moderate increase can occur in the compressive strength of fibre reinforced concrete due to a high strain-hardening response of fibres under tensile loading.…”
Section: Concrete Is One Of Most Popular Construction Materials and Imentioning
confidence: 99%
“…Furthermore, Jiang et al [ 103 ] found that longer fibers outperform shorter ones in improving splitting tensile and flexural strengths. Saradar et al [ 159 ] investigated the flexural strength of 12 mm long basalt, steel, glass, PP, and PO fibers with 0.1% of volume fraction. The study reported that all the fibers increased the flexural strength of concrete, however, basalt and steel fibers made the highest contribution followed by PO, glass, and PP fibers.…”
Section: Pre-peak Mechanical Propertiesmentioning
confidence: 99%
“…Once exposed, cracking would make the retrofitting unreliable if the beam was still exposed to the environment. Luckily, if the metal content and length are increased, shrinkage crack surfaces are considerably reduced, up to 86% compared to non-fiber specimens [24]. With timely crack detection, these cracks can be identified and repaired before significant damage to the inner fibers occurs.…”
Section: Uhpcmentioning
confidence: 99%